Integrated Configuration of Folding Wall-BIPV at Office Building in Surabaya as Low Carbon Building Design - Susan Susan (Humaniora, 2017)
This research would compare optimal configurations of Folding Wall-BIPV to flat wall-BIPV (as base case model). Experiment with simulation as it tools was used as a method to get the optimal configuration of Folding Wall-BIPV. Related to second strategy towards LCB (Low Carbon Building), this research calculated how much electricity energy was produced by renewable energy resource (created by the integrated configuration of folding wall-BIPV) could substitute electricity energy produced from fossil fuel and how much was the uniformity ratio generated from both side of Folding Wall-BIPV. This research used the experimental methods. The data was collected from Badan Meteorologi dan Geofisika Surabaya and then hold the pretest, treatment, and post-test condition for its methods. The result shows that integrated configuration of folding wall-BIPV match to the second strategies adopted by LCB. It is about switching to renewable energy sources to substitute fossil fuel energy sources.